2011
DOI: 10.16997/jdd.115
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Engagement Exercises: Exploring the U.S. National Citizens’ Technology Forum from the Bottom-Up

Abstract: Exercises intended to engage laypeople in deliberations about emerging scientific and technological issues have become very popular in recent decades. These exercises are typically organized by political or intellectual elites, and often assessed in a top-down fashion as well. This paper disrupts that pattern by using a mix of complementary qualitative approaches to explore the experiences of citizen participants in a large exercise on emerging technologies, the 2008 U.S. National Citizens Technology Forum (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…For instance, during my empirical research I have found that entertainment is implicit in the framing of informal public engagement, with organisers striving to design events which laypeople will, above all, attend, and ideally enjoy; that enjoyment is constantly cited by audiences and participants as a key feature of their experience (with interviews with these actors, at public engagement events or deliberative processes, almost invariably starting with some variation of: 'it's really good, I'm enjoying it'); and that the necessity of pleasurable aff ects is articulated with normative passion by communicators who argue not just that they know what their audiences want but that science-as-leisure can have profound eff ects on participants. Delight, interest, enthusiasm, and pleasure all leave their traces on the practice of public engagement (see also Pearson, 1997;Rowe et al, 2010;Simonsson, 2006;Wilkinson et al, 2011) -even those forms, such as consensus conferences, which are more formal, perhaps drier, in nature (Powell et al, 2011). It is worth, I think, running the risk of labouring this point.…”
Section: Knowing and Loving: Pleasure In Public Engagementmentioning
confidence: 99%
“…For instance, during my empirical research I have found that entertainment is implicit in the framing of informal public engagement, with organisers striving to design events which laypeople will, above all, attend, and ideally enjoy; that enjoyment is constantly cited by audiences and participants as a key feature of their experience (with interviews with these actors, at public engagement events or deliberative processes, almost invariably starting with some variation of: 'it's really good, I'm enjoying it'); and that the necessity of pleasurable aff ects is articulated with normative passion by communicators who argue not just that they know what their audiences want but that science-as-leisure can have profound eff ects on participants. Delight, interest, enthusiasm, and pleasure all leave their traces on the practice of public engagement (see also Pearson, 1997;Rowe et al, 2010;Simonsson, 2006;Wilkinson et al, 2011) -even those forms, such as consensus conferences, which are more formal, perhaps drier, in nature (Powell et al, 2011). It is worth, I think, running the risk of labouring this point.…”
Section: Knowing and Loving: Pleasure In Public Engagementmentioning
confidence: 99%